Simple Synthesis of 2-Aminoaryliminophosphoranes from N-Aryl-2-nitrosoanilines and Their Application in 2-Aminobenzimidazole Synthesis - Łukasik, Emilia; Wróbel, Zbigniew (Synlett, 2014)
Condensation of N-aryl-2-nitrosoanilines with triphenylphosphine leads efficiently to substituted aryliminophosphoranes which, in turn, react with alkyl isocyanates furnishing 2-alkylaminobenzimidazole derivatives in high yields.
Keywords: cyclization; condensation; heterocycles; annulation